Business Model of Established Publisher Analysis to Conduct New Business Model for Ataru Publisher - Suadiani, Risa; Ratnaningtyas, Sudrajati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Publishing business is one of creative industry which grow rapidly, especially in Bandung city. As we know, Bandung is famous as a â€œcreative cityâ€. That is why there are so many creative and innovative business in Bandung such as fashion and culinary. Include publishing business. Despite being hit with technological developments bit much harm business book publishers, but publishers still businesses can adapt to the technology even use technological advances and information to run their business. Ataru as a new player in this business quite stumbled in running the business. Ataru main problems facing today is a business model that is less feasible. In this final project will be presented shortage of Ataru of the business model was not relevant applied this current publishing business condition. The aim of this research is to conduct new business model for Ataru. Kaifa Publisher is a book publishing company that was founded in 2012 and be a role model for Ataru to improve its business model. The results of the identification of this business model will then be compared with the business model of Ataru to see where the weak parts of the business owned Ataru. After obtained the results of the analysis of the gap between Kaifa and Ataru, researchers will adapt the business model of Kaifa Publisher with Ataru as a new business model. Researchers will not implement the whole business model of Kaifa on Ataru without adjustment, but adjust Ataru capabilities in terms of capital and resources. After that, it is expected to be able to run back Ataru business book publisher with a new business model that is better than the previous model. From this new business model, the researchers derive each business aspect into the implementation plan. This implementation plan will be used to run a new business model Ataru.Â Keywords: business model, book publisher, role models, Bandung, creative industries